Profile of Post Preschool Teachers in Semarang, Reviewed from Competence Pedagogy - ., Rasiman; Koyimah, Siti (KnE Social Sciences, 2024)
The majority of post-preschool educators in Semarang City have an educational background at the high school level, namely 806 people out of 1181 people. This causes a lack of pedagogical competence for post-pre-school teachers. The research objective is to analyze the profile of Semarang City post-pre-school educators in terms of pedagogical competence. This research uses a mix of qualitative and quantitative methodology. Data collection techniques used were documentation, questionnaires, and interviews. The participants were 88 teachers and two respondents. Research results, educator profile of pedagogical competency: from the results of the quantitative analysis, it was concluded that the majority of educators had pedagogical competence in the medium category at 77.3%, while the high category reached 12.5%, and low competence at 10.2%. These results are reinforced by qualitative analysis: educators must have the knowledge, skills, and attitude needed in the learning process; they can design and implement effective learning activities and encourage the development of young children. In addition, educators must have a strong commitment to ethical and professional standards, and best practice skills in early childhood education. Keywords: post pre-school, competence, pedagogy